The hollow ones - Toro, Guillermo del, 1964-; Hogan, Chuck (Toro, Guillermo del, 1964- Blackwood tapes, 2020)
Forced to shoot her suddenly violent partner, rookie FBI agent Odessa Hardwicke witnesses the escape of a shadowy form from the deceased agent's body, and embarks on a sanity-risking investigation into a centuries-old being.